An Analysis Of The Impact Of Price, Facilities, And Service On Customer Loyalty At Fitnation Semarang - Abel Varian Setiadi; MY Dwi Hayu Agustini (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research explores the role of pricing, available facilities as well as the level of service excellence in shaping customer loyalty at Fitnation Semarang.Using a quantitative approach, information was gathered via a structured survey and subjected to multiple linear regression analysis. The study, which included 100 active members as responders, found that consumer loyalty is statistically significantly impacted by pricing, facilities, and service taken together. Individually, facilities and service exhibit a positive and significant relationship, whereas price demonstrates a significant negative correlation. The model yields an adjusted R square of 0.865, indicating 86.5% of the variation found in customer loyalty might be attributed to these three independent variables. The study highlights the need to enhance service and facility quality while reviewing pricing strategies to foster stronger customer/client loyalty.